UMUR BALITA DAN STATUS IMUNISASI PENTABIO (DPT HB-Hib) DENGAN KEJADIAN ISPA PADA BALITA - Nadya Sari Komala; Muhammad Mukhtar; Rubiati Hipni; Erni Setiawati (MMJ (Mahakam Midwifery Journal), 2022)
Abstract The Prevalence of ARI in the last few months was spread across the province of South Kalimantan, amounting to 27,1%, ranging from 13,2%-42,3%. There are 7 districts/cities that exceed the prevalence rate of prevention, namely Balangan (42,3%), Barito Kuala (41%), Hulu Sungai Selatan (36,6%), Tapin (36,5%), Banjar (30%), Tanah Laut (27,4%) and Tanah Bumbu (27,2%). There is only 1 district with the lowest ARI prevalence rate, namely Hulu Sungai Tengah (0,2%) (Riskesdas, 2018). The purpose of this study ws to determine the relationship between toddlers age and status immunization of pentabio (dpt-hb-hib) with the incidence of ari in toddlers in the work area of the Giri Mulya care center, Tanah Bumbu regency in 2020. This research method is an analytic survey with a cross sectional approach. The population in this study were all respondent who were takeen from the register book in the IMCI room, amounting to 320 respondents. This research instrument uses a register book in the IMCI room. The result of this study by processing the data using the Chi Square test showed the value of ρ = 0,000 (ρ 0,05) for the age of toddlers and ρ = 0,494 (ρ >α > 0,05) for status immunization of pentabio (dpt-hb-hib). The conclusion in this study is that there is a relationship between toddlers age and status immunization of pentabio (dpt-hb-hib) with the incidence of ari in toddlers in the work area of the Giri Mulya care center, Tanah Bumbu regency in 2020. Keywords : Toddlers Age, Status Immunization of Pentabio, ARI Abstrak Prevalensi ISPA beberapa bulan terakhir tersebar di Provinsi Kalimantan Selatan berjumlah 27,1% rentan 13,2% - 42,3%. Ada 7 kabupaten/kota yang melebihi angka prevalensi provinsi yaitu Balangan (42,3%), Barito Kuala (41%), Hulu Sungai Selatan (36,6%), Tapin (36,5%), Banjar (30%), Tanah Laut (27,4%) dan Tanah Bumbu (27,2%). Hanya ada 1 kabupaten yang angka prevalensi ISPA paling rendah yaitu Hulu Sungai Tengah (0,2%) (Riskesdas, 2018). Tujuan penelitian ini adalah untuk mengetahui hubungan umur balita dan status imunisasi Pentabio (DPT-HB-Hib) dengan kejadian ISPA pada balita di Wilayah Kerja Puskesmas Perawatan Giri Mulya Kabupaten Tanah Bumbu Tahun 2020. Metode penelitian ini adalah survey analitik dengan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah seluruh responden yang diambil dari buku register di ruang MTBS yang berjumlah 320 responden. Instrumen penelitian ini menggunakan buku register di ruang MTBS. Hasil penelitian ini dengan olah data menggunakan Uji Chi Square menunjukkan nilai ρ = 0,000 (ρ 0,05) untuk Umur Balita dan ρ = 0,494 (ρ >α > 0,05) untuk Status Imunisasi Pentabio (DPT-HB-Hib). Kesimpulan dari penelitian ini adalah ada hubungan Umur Balita dan Status Imunisasi Pentabio (DPT-HB-Hib) dengan kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Perawatan Giri Mulya Kabupaten Tanah Bumbu Tahun 2020. Kata kunci : Umur Balita, Status Imunisasi Pentabio, ISPA